Symbionts modify interactions between insects and natural enemies in the field - Hrček, Jan; McLean, Ailsa H C; Godfray, H Charles J (The Journal of animal ecology, 2016)
Eukaryotes commonly host communities of heritable symbiotic bacteria, many of which are not essential for their hosts' survival and reproduction. There is laboratory evidence that these facultative symbionts can provide useful adaptations, such as increased resistance to natural enemies. However, we do not know how symbionts affect host fitness when the latter are subject to attack by a natural suite of parasites and pathogens. Here, we test whether two protective symbionts, Regiella insecticola and Hamiltonella defensa, increase the fitness of their host, the pea aphid (Acyrthosiphon pisum), under natural conditions. We placed experimental populations of two pea aphid lines, each with and without symbionts, in five wet meadow sites to expose them to a natural assembly of enemy species. The aphids were then retrieved and mortality from parasitoids, fungal pathogens and other causes assessed. We found that both Regiella and Hamiltonella reduce the proportion of aphids killed by the specific natural enemies against which they have been shown to protect in laboratory and cage experiments. However, this advantage was nullified (Hamiltonella) or reversed (Regiella) by an increase in mortality from other natural enemies and by the cost of carrying the symbiont. Symbionts therefore affect community structure by altering the relative success of different natural enemies. Our results show that protective symbionts are not necessarily advantageous to their hosts, and may even behave more like parasites than mutualists. Nevertheless, bacterial symbionts may play an important role in determining food web structure and dynamics.
Keywords: houby; Symbiosis; sršňovití; field experiment; Fungi; symbiosis; aphid; Aphids; Host-Pathogen Interactions; Enterobacteriaceae; host-pathogen; Wasps; zvířata; interactions; interakce hostitele a patogenu; symbióza; Host-Parasite Interactions; mšice; genetická zdatnost; interakce hostitele a parazita; Genetic Fitness; host-parasite; Animals